Stability Of Thin Liquid Film Under Effect Of Apolar And Electrostatic Forces On A Horizontal Plane - El-Harbawi, Mohanad M-A. (2002)
The understanding of stability, dynamics and morphology of supported th (<100nm) liquid films and nanodrops are important in phenomena like flotation, adhesion of fluid particles to surfaces, kinetics and thermodynamics of precursor films in wetting, heterogeneous nucleation, film boiIing/condensation, multilayer adsorption/film pressure, instability of biological films/membranes, and many other areas While the wetting of surface by large drops is relatively well understood, wetting charactenstics of nanodrops and films have not been extensively studied in some applications like trickle bed reactors, thick coating, contact equipment for heat and mass transfer. and the like Factors that would affect the total free excess energy (per unit area) of a thin film on a substrate include the film thickness, as well as the apolar and electrostatic spreading coefficients for the system. The dynamics of the liquid film is formulated using the Navier-Stokes equations augmented by a body forces describing the apolar and electrostatic interactions.